Urgensi Akhlak Bagi Guru dalam Menjalani Kehidupan di Era Society 5.0 - Muhammad Ichsan (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
In the current era of Society 5.0, talking about the urgency of morality, especially for teachers, is an interesting matter, where with the current dynamics, many teachers do not understand the urgency of morality, so they do not show noble character, that is, they cannot be an example for students or society. Therefore, the importance of these morals needs to be known and learned and practiced in everyday life so that they can continue to improve themselves and their people in a better direction. Morals are conditions or characteristics that are imprinted and seep into the soul, so that the perpetrator of the deed does something spontaneously and easily without making it up. Morals according to the understanding of Islam is one of the results of faith and worship, because human faith and worship are not perfect unless noble morals emerge from them. Therefore, morality in Islam is rooted in faith and piety and has a direct goal, a close one, namely self-esteem and a distant goal, namely the pleasure of Allah SWT. Among the goals of education is to form good morals in children and this is only possible if the teacher has good morals too. This means that morals are in accordance with Islamic teachings, as exemplified by the main educator, namely the Apostle Allah Muhammad Saw. As for the moral urgency for educators (teachers) in life in the 5.0 era, they include: 1) Increasing the degree of piety, 2) Encouraging goodness, 3) Perfection of faith, 4) Virtue in the afterlife, and 5) Getting along with neighbors.